Does the intubation timeline affect the in-hospital mortality of COVID-19 patients? A retrospective cohort study - Rehman, Shazia; Shahiman, Muhammad Ali; Khaleel, Mundher A; Holý, Ondřej (Frontiers in medicine, 2022)
BACKGROUND: Effective strategies for managing coronavirus disease 19 (COVID-19) patients suffering from acute respiratory distress are constantly evolving. The timeline and threshold for transitioning from non-invasive ventilation to intermittent mandatory ventilation in critical cases who develop COVID-19-related respiratory distress are undetermined. The present research intends to investigate if emergency room intubations in COVID-19 patients affect mortality. METHODS: Between January 1, 2021 and June 30, 2021, we retrospectively reviewed chart analysis on all patients with confirmed positive COVID-19 screening and who underwent endotracheal intubation. Depending on when the intubation was performed; early in the emergency room or delayed outside the emergency room, patients were separated into two cohorts. In addition to comorbid clinical manifestations, the quick sequential organ failure assessment (qSOFA) score, and in-hospital mortality were all recorded as demographic and clinical information. RESULTS: Fifty-eight of the 224 corona-positive patients who underwent intubation had their intubations performed in the emergency room. Age, sex, alcohol use, and smoking status did not significantly differ between the two categories at the baseline. The mean qSOFA score was higher in the early intubation cohort (3.5; p < 0.000) along with more underlying comorbidities (3.0; p < 0.000). When compared to the late intubation cohort (45.78%), patients treated with early intubation had a significantly greater death rate (67.24%). CONCLUSION: In summary, we discovered that patients who underwent intubation in the emergency units exhibited a high quick SOFA score as well as maximum co-morbid conditions than patients intubated somewhere else in the hospital. The findings of our investigation imply that intubating patients too early might be risky.
Keywords: COVID-19; emergency unit; early intubation; acute respiratory failure; late intubation